Ionic Liquids Current State of the Art - Handy, Scott (IntechOpen, 2015)
Ionic liquids continue to attract a great deal of research attention in an even increasing number of areas, including more traditional areas such as synthesis (organic and materials) and physical properties studies and predictions, as well as less obvious areas such as lubrication and enzymatic transformations. In this volume, recent advances in a number of these different areas are reported and reviewed, thus granting some appreciation for the future that ionic liquids research holds, and affording inspiration for those who have not previously considered the application of ionic liquids in their area of interest.